1999
DOI: 10.1086/312046
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of New and Old Magnetic Fluxes at the Beginning of Solar Cycle 23

Abstract: The 11-year cycle of solar activity follows Hale's law by reversing the magnetic polarity of leading and following sunspots in bipolar regions during the minima of activity. In the 1996-97 solar minimum, most solar activity emerged in narrow longitudinal zones -'active longitudes' but over a range in latitude. Investigating the distribution of solar magnetic flux, we have found that the Hale sunspot polarity reversal first occurred in these active zones. We have estimated the rotation rates of the magnetic flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 14 publications
5
61
0
1
Order By: Relevance
“…It has been found that various manifestations of solar activity, such as sunspots (Berdyugina et al 2003;Usoskin et al 2005;Juckett 2006), solar magnetic field (Benevolenskaya et al 1999;Bumba et al 2000), heliospheric magnetic field (Ruzmaikin et al 2001;Takalo & Mursula 2002;Mursula & Hiltula 2004), and flares (Bai 1988(Bai , 2003 occur preferentially at specific longitudes that are called active longitudes. However, lifetimes and rotation velocities of active longitudes obtained for different tracers of solar activity have been found to vary significantly.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that various manifestations of solar activity, such as sunspots (Berdyugina et al 2003;Usoskin et al 2005;Juckett 2006), solar magnetic field (Benevolenskaya et al 1999;Bumba et al 2000), heliospheric magnetic field (Ruzmaikin et al 2001;Takalo & Mursula 2002;Mursula & Hiltula 2004), and flares (Bai 1988(Bai , 2003 occur preferentially at specific longitudes that are called active longitudes. However, lifetimes and rotation velocities of active longitudes obtained for different tracers of solar activity have been found to vary significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of EIT synoptic maps for 171A, 195A, 284A and 304A for CR1935 are presented in Figure 1. (Benevolenskaya et al 1999). However, the large-scale stable longitudinal patterns are better seen on the coronal maps than on the magnetic maps.…”
Section: Eit Synoptic Mapsmentioning
confidence: 93%
“…Studying rotation of the 'old' and 'new' fluxes and comparing their rotation rates with the internal rotation obtained by helioseismology we have suggested that both fluxes are probably generated in a narrow low-latitude zone of the tachocline (Benevolenskaya et al 1999) -the region of the steep radial gradient of solar rotation at the bottom of the convection zone, where the magnetic flux is probably generated (e.g. Parker, 1993).…”
Section: Conclusion 253mentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the now popular idea of flux-transport dynamos where the meridional circulation is chiefly responsible for the equatorward migration of the toroidal flux belts (see article by M. Dikpati in this issue). However, in recent years it became clear that in the outer 5% of the Sun by radius there is strong negative radial shear (Benevolenskaya et al 1999), which could in principle also explain the equatorward migration in the framework of conventional solar dynamo theory (B05). On the other hand, such a theory also faces problems of its own, for example the latitudinal width of the flux belts is expected to be only a few times bigger than the depths of the supergranulation layer ), which would be too small.…”
Section: Helioseismology: Overshoot Layer and Flux-transport Dynamosmentioning
confidence: 99%